Myxedema Psychosis: Neuropsychiatric Manifestations and Rhabdomyolysis Unmasking Hypothyroidism. (22nd June 2020) - Sardar, Sundus; Habib, Mhd-Baraa; Sukik, Aseel; Tanous, Bashar; Mohamed, Sara; Tahtouh, Raad; Hamad, Abdelrahman; Mohamed, Mouhand F. H.
Abstract : Background . Hypothyroidism is a prevalent endocrine disorder, often presenting with a spectrum of symptoms reflecting a hypothyroid state. It is also generally linked to causing mood swings, psychomotor slowing, and fatigue; however, in rare instances, it may lead to or induce acute psychosis, a condition referred to as myxedema psychosis (MP). We report a case of myxedema psychosis and present a literature review discussing its presentation, diagnosis, management, and prognosis. Case Presentation . A 36-year-old lady presented with one-week history of persecutory and paranoid delusions, along with visual and auditory hallucinations. She had no prior history of psychiatric illnesses. She underwent total thyroidectomy three years before the current presentation due to papillary thyroid cancer. She was not on regular follow-up, nor any specific therapy. On examination, she was agitated and violent. There were no signs of myxedema, and the physical exam was unremarkable. The initial workup showed a mild elevation in serum creatinine. Additional investigations revealed a high thyroid-stimulating hormone (TSH) of 56.6 mIU/L, low free T 4 < 0.5 pmol / L, elevated creatine kinase of 3601 U/L, and urine dipstick positive for blood, suggestive of myoglobinuria. MRI of the head was unremarkable. We diagnosed her as a case of myxedema psychosis and mild rhabdomyolysis. She was started on oral thyroxine 100 mcg/day, fluoxetine 20 mg daily, and as-needed haloperidol. She was closely followed and later transferred to the Psychiatry Hospital for further management. Within one week, her symptoms improved completely, and she was discharged off antipsychotics with additional scheduled follow-ups to monitor TFTs and observe for any recurrence. Discussion and Conclusion . Myxedema psychosis is a rare presentation of hypothyroidism—a common endocrine disorder. Scarce data are describing this entity; hence, there is currently a lack of awareness amongst clinicians regarding proper identification and management. Moreover, the atypical nature of presentations occasionally adds to a diagnostic dilemma. Thus, any patient with new-onset psychosis should be screened for hypothyroidism, and awareness of this entity must be emphasized amongst clinicians and guideline makers.